Ion implantation of 226Ra for a primary 222Rn emanation standard. (March 2022) - Mertes, Florian; Kneip, Nina; Heinke, Reinhard; Kieck, Tom; Studer, Dominik; Weber, Felix; Röttger, Stefan; Röttger, Annette; Wendt, Klaus; Walther, Clemens
Abstract: Laser resonance ionization at the RISIKO 30 kV mass separator has been used to produce isotopically and isobarically pure and well quantified 222 Rn emanation standards. Based upon laser-spectroscopic preparation studies, ion implantation into aluminum and tungsten targets has been carried out, providing overall implantation efficiencies of 40% up to 60%. The absolute implanted activity of 226 Ra was determined by the technique of defined solid-angle α-particle spectrometry, where excellent energy resolution was observed. The 222 Rn emanation coefficient of the produced targets was studied using α-particle and γ-ray spectrometry, and yielded results between 0.23 and 0.34, with relative uncertainty on the order of 1%. No dependence exceeding a 1% change of the emanation on humidity could be identified in the range of 15 %rH to 75 %rH, whereas there were hints of a slight correlation between the emanation and temperature. Additionally, and as expected, the emanation coefficient was found to be dependent on the target material as well as the implanted dose. Highlights: Laser ionization ion implantation was used to implant 226 Ra ions into metallic supports at an implantation energy of 30 keV. Implantation efficiencies up to 60% were achieved. The emanation of 222 Rn from thus implanted 226 Ra was investigated by gamma-ray- and alpha-particle spectrometry. Emanation coefficients are well reproducible and deviate slightly from theoretical considerations demonstrating a target material dependency. 222 Rn emanation from the sources is stable concerning relative humidity, but slightly dependent on temperature.